Evaluation of Nurses' Skills on Changing the Central Venous Catheter Dressing for Patients in Baghdad Teaching Hospitals - Alaa Jawad Kadhim, Ahmed F. Hassan, Safad R. Isam (Drugs and Cell Therapies in Hematology, 2021)
A central venous catheter is a long, flexible, thin hollow tube placed into a main vein (a blood vessel). Like an intravenous catheter implanted in an arm vein, the centre line is longer and placed in a large vein in the neck, upper chest, or leg that leads to the heart. Objectives:This study aimed to evaluate of nurses' skills on changing the central venous catheter dressing for patients. Methodology: A descriptive study was done April 15 and July 17, 2021 in Baghdad Teaching Hospitals to assess nurses' proficiency in changing central venous catheter dressings and their demographic characteristics. Forty nurses from Baghdad's teaching hospitals were chosen at random (Baghdad Teaching Hospital and Al Kindi Teaching Hospital). Descriptive statistics were extensively used in the Sixteenth Edition of the Statistical Portfolio for Social Sciences. Results:The study found that the final assessment of the paragraphs of the survey (20) to evaluate nurses' competence in changing central catheter dressings for patients at the lowest level. Conclusion:according to this study, the majority of nurses practiced at a poor level. Recommendation:The study recommended the necessity of designing a special program to train all nurses who work in Baghdad teaching hospitals to increase the nurses’ skills with regard to changing the central venous catheter dressing for patients, and issuing a summary booklet on changing the central venous catheter dressing and distributing it to all nurses of Baghdad teaching hospitals and designing guidance leaflets in cooperation with the Ministry of Health on How to change the dressing of the central venous catheter.